Thermoplastic Analysis of Cluster Crystallization of Cryoprotective Solutions - Osetskyi, Oleksandr; Gurina, Tetyana; Poliakova , Anna; Sevastianov , Stanislav (Problems of Cryobiology and Cryomedicine, 2021)
For the first time the possibility of using thermomechanical analysis to construct the fragments of state diagrams of cryoprotective solutions in the zone of glass transition temperatures has been considered. A method for studying cluster crystallization of cryoprotective solutions based on thermomechanical curves has been developed. The parameters of thermomechanical curves of frozen aqueous solutions of dimethyl sulfoxide (DMSO), polyethylene oxide 1500 (PEO-1500), glycerol were analyzed and the relationship between these parameters and the cluster crystallization kinetics for these solutions was established. On the basis of experimentally obtained thermomechanical curves for the frozen solutions of DMSO and PEO-1500 the possibility of formation of clusters of two types has been shown: on the basis of ice and cryoprotective substance microcrystals. Additional experimental data were obtained to construct a complete state diagrams of cryoprotective solutions, which include the existing cluster phase areas. Probl Cryobiol Cryomed 2021; 31(3): 203–213